The effect students in emotional distress have on their residence hall roommate - Caron, Stephanie Lynne (Kansas State University, 2010)
Since residence hall roommates can have a significant effect on the stress level of an individual, it was predicted that living with a roommate experiencing emotional distress could cause added stress due to the support needs of that roommate. For this study, emotional distress is defined as experiencing any of the following symptoms of common mental illness: excessive use of alcohol/drugs; working hard but getting poor grades; test anxiety; excessive tearfulness or crying; feeling misunderstood or mistreated; lost hope that life will improve; unresolved conflicts with others; feeling agitated or restless; having trouble memorizing; difficulty concentrating, focusing, or paying attention; bored or unhappy with life; loss of energy/fatigued; feeling shy or timid; excessive worry; change in nutrition or exercise habits; low self-esteem; difficulty trusting other people; lost interest in activities; changes in sleep patterns; no close personal friends (lonely); poor time management; mood swings; difficulty controlling angry thoughts or actions; anxiety attacks; depressed mood; and/or addiction concerns (Robertson, 2006). A qualitative research study was done where five individuals were interviewed about their experience living with someone who was experiencing emotional distress. The participants’ answers were evaluated and synthesized with prior research material. Further research could be done on this subject by utilizing quantitative research methods at multiple institutions and comparing the results with the institutions’ policies and procedures for staff members. This research could result in a new manner in which to respond to students who are experiencing emotional distress and to their roommates in the residence halls.
Keywords: mental health; residence halls; roommate; college student; depression; FERPA; Education, Higher (0745)